Antitubercular cassane furanoditerpenoids from the roots of Caesalpinia pulcherrima - Promsawan N. (2014)
Activity-guided fractionation of a root extract of Caesalpinia pulcherrima led to the isolation of two cassane-furanoditerpenoids, 6β-benzoyl-7β -hydroxyvouacapen-5α-ol (1) and 6β-cinnamoyl-7β -hydroxyvouacapen-5α-ol (2). Compound 2 showed strong antitubercular activity with a minimum inhibitory concentration (MIC) of 6.25 μg/mL, whereas the benzoyl analogue (1) was less active (MIC 25 μg/mL). Both compounds expressed moderate cytotoxic activity towards KB (human oral carcinonoid cancer), BC (human breast cancer) and NCI-H187 (small cell lung cancer) cell lines.